Police Violence and Corruption in the Philippines: Violent Exchange and the War on Drugs - Steffen Jensen; Karl Hapal (Journal of Current Southeast Asian Affairs, 2018)
In this article we explore the relationship between money and violence in the Philippine war on drugs. Building on long-term ethnographic and political engagement with a poor urban neighbourhood in Manila, we suggest that while the war on drugs has taken state killings to a new level, the Philippine state was no stranger to killing its own citizens before its onset. Furthermore, we argue that we cannot dissociate the killings from the rampant corruption in the Philippine police. By invoking the concept of violent exchange, the article shows that both corruption and death enter into particular understandings of state–citizen relationships. Because the war has reconfigured how death and corruption work, people in urban Manila are attempting desperately – as the stakes are high – to figure out how to engage with the police under these transforming conditions.